Spontaneous Uterine Rupture at 15 Weeks' Gestation in a Patient with a History of Cesarean Delivery after Removal of Shirodkar Cerclage - Serika Kanao; Aya Fukuda; Hirotsugu Fukuda; Mayuko Miyamoto; Eriko Marumoto; Kiichiro Furuya; Rie Nishiyama; Chifumi Ohyagi; Haruki Ogawa (Thieme Medical Publishers, Inc., 2014)
Abstract A pregnant woman presented with acute upper abdominal pain and nausea at 15 weeks' gestation. She had a history of cesarean delivery for abruption after the removal of a Shirodkar cerclage that was placed because of cervical shortening caused by conization. She became pregnant again 14 months later. Ultrasonography revealed no significant findings, and a single intrauterine pregnancy with positive fetal heart activity was confirmed. An intestinal obstruction was suspected because abdominal radiography showed multiple air-fluid levels in the colon. Over the 3 hours following admission, her symptoms gradually worsened, and plain abdominal computed tomography (CT) showed a large hemorrhage in the abdominal cavity, but the uterine wall appeared intact at this time. Subsequently, dynamic CT revealed discontinuity of the uterine muscle layer. During laparotomy, uterine rupture with complete opening of the uterine wall at the site of the previous transverse scar was identified. A dead fetus was located within the amniotic sac in a blood-filled abdominal cavity. She received a total of 10 units of packed red blood cells and 6 units of fresh frozen plasma for the resuscitation. She was discharged on the eighth postoperative day without any complications.